Radial Centrifugal Fan Redesign and New Technologies Using CFD Applications - Budea, Sanda; Iordan, Ion-Bogdan (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The purpose of this article is to redesign centrifugal radial fans used in HVAC installations, using the analysis of aerodynamic flows and velocities distributions in the fan. Numerical simulations based on the reference model from the Pumps and Fans laboratory were performed using the SolidWorks program, Flow Simulation module. Following the simulations, information regarding the fluid flow in the machine rotor and casing, the most suitable shape of the blades resulted, and redesign solutions through 3D printing technologies were proposed. Numerical simulations with Flow Simulation on three-dimensional models were carried out, for a better analysis of the volume of air passing through the fan, but also for the prediction of some negative effects: the appearance of vortices that lead to high noises/acoustic disturbances, the appearance of additional vibrations, but also sudden and uncontrolled variations in the pressure force. Following the numerical analysis, it was found that for the new blade profiles the velocities are uniform, which greatly reduces the noise and vibrations in the operation of the fan. The redesign also aims to reduce the energy consumption of these fans.